Analysis Of Macroeconomic Conditions On The Performance Of Protected Mutual Funds In Indonesia In Moderated Age And Size Of Mutual Funds For The Period January 2018 – August 2023 - Tinjung Desy Nursanti; Nugraha; Ika Putera; Maya Sari; Erric Wijaya (Universitas Udayana, 2024)
This study aims to find evidence whether Macroeconomic Conditions can affect the Performanceof Protected Mutual Funds in Indonesia which is Moderated Age and Size of Mutual Funds forthe period January 2018 – August 2023. The motivation for this study comes from identifying therelationship between macroeconomic conditions and mutual fund performance simultaneously isvery important because it has significant implications in efforts to improve mutual fundperformance against macroeconomic conditions. However, there are limitations to empiricalstudies on the impact of these mutual funds because the data year series is limited to only a fewyears. Using the Random Effect Model (REM) panel regression method approach, the analysisperiod from January 2018 to August 2023 panel data on macroeconomics and mutual funds, itwas found that macroeconomic variables of the rupiah exchange rate against the US dollar (NT)had a significant influence on the performance of the highest mutual funds measured by the sharperatio. Meanwhile, macroeconomic variables that do not have a significant influence on theperformance of protected mutual funds are interest rate (SBI) and inflation (INF) variables. Thevariable age and size of mutual funds have a significant influence on the performance of protectedmutual funds. In addition to these independent variables, this study also used moderator /moderating variables. Moderator variables to see the interaction relationship between moderatorvariables and predictor variables (independent). Moderator variables are variables that canstrengthen or weaken the relationship between independent and dependent variables. Themoderator variables of this study are age and size of mutual funds